Determination the Natural Radioactivity in some Building Materials (Latakia University Journal -Basic Sciences Series, 2021)
In this work, exhalation rate of radon gas was determined in some building materials used in cladding in Syria and carried out in the Lattakia governorate, using the technique of counting the alpha particles emitted from radon gas in the nuclear impact detector (CR-39). The results obtained show that the highest exhalation rate of radon gas is recorded for the California granite (19.94 ± 1.65) Bq.m-2.d-1 and the lowest value for white Cement was (0.13 ± 0.02) Bq.m-2.d-1.The research also included determining the natural radioactivity through the gamma spectroscopy using a high-purity Germanium detector where the radium-226 activity is determined in the studied building materials and some other isotopes. We find that the highest rate of effective radium content is the California granite (192 ± 6.2) Bq/kg and The lower rate attributed to the Turkish Mola marble (2.2±0.4) Bq/kg and this is consistent with the results exhalation of radon gas, we conclude that there is a correlation between the concentration of radium and the exhalation rate of radon gas from building materials.